Biofortification of Vegetable Crops: An Option for Mitigating Hidden Hunger - Kumari, Manisha; Sharma, Deepa; Sandeep, Sampathi (International Journal of Economic Plants, 2022)
Micronutrient malnutrition is known to affect more than half of the world’s population and considered to be among the most serious global challenges to humankind. One such approach to combat the issue of micro nutrient malnutrition is through biofortification, a process of breeding nutrients into food crops which provides a comparatively cost-effective, sustainable and long-term means of delivering more micronutrients to rural populations in developing countries. Biofortification of vegetables with vitamins and micronutrients is the present day need for developing countries to overcome various health issues. Currently, agronomic conventional plant breeding and genetic modification are three common approaches for biofortification of vegetable crops. Agronomic biofortification is the application of fertilizers to increase the micronutrients in edible parts. Iron level of Amaranthus plants can be increased by using Spirulina platensis as microbial inoculant when compared with control. In conventional plant breeding, parent lines with high vitamin or mineral levels can be crossed over several generations to produce plants that have the desired nutrients. IARI, New Delhi developed first ever indigenously bred biofortified beta carotene (8–10 μg g-1) rich cauliflower variety i.e. Pusa Betakesari-1 through marker assisted backcrossing. Transgenic approaches are advantageous when the nutrient does not naturally exist in a crop. Increased nutritive value in potato may be achieved by expressing a non-allergenic seed albumin gene from Amaranthus hypochondriacus by protein-rich potato expressing the seed protein gene AmA1 (Amaranth Albumin 1). Many genes are available for the target traits by which it will be possible to enhance micronutrient in vegetables. These approaches can be very much helpful in improving the level of micronutrients and vitamins by several-fold in different vegetables.